STABILITAS KIMIA DAN USIA SIMPAN SIRUP PARASETAMOL PADA BERBAGAI SUHU PENYIMPANAN - Zulkarnain, Iskandar (Fakultas Farmasi UMI, 2014)
Paracetamol syrup used to treat the symptoms of an illness and is often used as a stock. Chemical stability during storage is important to know. This study aims to determine the half-life of paracetamol syrup and store age. Stability testing performed on 4 kinds of paracetamol syrup that is Generic A and B, and C and D. Each issued its contents syrup 30 ml and stored at room temperature and refrigerator temperature. For comparison there are also groups syrup without treatment. After that stability testing. The method of testing is done by an accelerated stability test that samples stored at 40oC, 50oC, and 60oC for 4 days and then determined the concentration of paracetamol syrup every day. Age store (t90) obtained from the results of the study for paracetamol syrup A generic product without treatment, room temperature and the temperature in the refrigerator is 3.44237, 2.42564 in, 0.66226 years. For paracetamol syrup generic product B without treatment, room temperature and the temperature in the refrigerator is 2.38027, 1.52801 in, 0.34438 years. For paracetamol syrup product patent C without treatment, room temperature and refrigerator temperature is 4.98265 in, 4.09024 in, 3.59095 years. For paracetamol syrup patent product D without treatment, room temperature and refrigerator temperature is 4.14238 in, 3.44643 in, 2.70283 years. So it can be known that paracetamol syrup stored at room temperature more stable.